2011
DOI: 10.1103/physreva.83.022710
|View full text |Cite
|
Sign up to set email alerts
|

High-charge-state limit for the double-to-single ionization ratio of helium in the strong-coupling regime

Abstract: We measured the double-to-single-ionization ratios R of helium impacted by the intermediate velocity C 4+ ion and found that R decreases as 1/v. This type of velocity dependence is consistent with the data for very highly charged ions (N 7+ ∼ U 92+ ). The charge state and velocity dependences of R are interpreted well by the classical over-barrier-ionization (COBI) model. It is found that the ratio R can be written in a manner of R = 0.28 √ q/v for very high-q projectiles in the strong coupling (q/v > 1) regim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…We recently noted this [24,25] and attempted to interpret the proton and antiproton data solely in terms of the first-order SO and TS1 mechanisms, which were assumed to interfere. We note that Shao et al also found a v −1 behavior for conditions where Z/v >1 [22,23]. To investigate the different velocity dependences for the Z = 1 and higher-Z projectiles, plus to fully test the first-and second-order interference model of McGuire, the experimental asymptotic high-energy ratio, which is assumed to be entirely first order, R 1st (Ý) = 0.002 59 [7], was subtracted from each experimental R 2 value in Fig.…”
Section: Analysis Proceduresmentioning
confidence: 86%
See 1 more Smart Citation
“…We recently noted this [24,25] and attempted to interpret the proton and antiproton data solely in terms of the first-order SO and TS1 mechanisms, which were assumed to interfere. We note that Shao et al also found a v −1 behavior for conditions where Z/v >1 [22,23]. To investigate the different velocity dependences for the Z = 1 and higher-Z projectiles, plus to fully test the first-and second-order interference model of McGuire, the experimental asymptotic high-energy ratio, which is assumed to be entirely first order, R 1st (Ý) = 0.002 59 [7], was subtracted from each experimental R 2 value in Fig.…”
Section: Analysis Proceduresmentioning
confidence: 86%
“…They attributed the remaining discrepancies to the lack of correlation in their model. A different model based up the strong electric field of the projectile leading to ejection or capture of target electrons has also been proposed [22,23], but its range of application should be limited to regions where Z/v is large and, in contrast to the McGuire and several other models, has no explicit first-order and second-order interference contributions to explain the observed differences in double ionization resulting from positive-and negativeprojectile impact.…”
Section: Introductionmentioning
confidence: 98%
“…Our ME-COBI model is based on COBI [22][23][24][25][26] and the over barrier (OB) models. [5] According to the capture model of OB, one electron can be released from the target atom when the Coulomb force is lower than the binding force of the electron in the atom.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…To understand the result, we analyze the ionization probability for the impact parameter b = 0. The ionization cross section is given by [24,26] σ k+ ≈ πR 2 Ik P k+…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…[13] [14] [15][16] to interpret the relative multiple ionization cross sections of Ar impacted by He + ions at energies from 10 to 800 keV/u, and by 34 MeVCl q+ . Now, we extend our previous work of COBI model to the multi-electron systems, and calculate the multiple ionization of Ne and CO molecule collided by very high-q fast projectiles in a strong coupling regime.…”
mentioning
confidence: 99%